CREBBP is a target of epigenetic, but not genetic, modification in juvenile myelomonocytic leukemia. Issue 1 (December 2016) - Fluhr, Silvia; Boerries, Melanie; Busch, Hauke; Symeonidi, Aikaterini; Witte, Tania; Lipka, Daniel; Mücke, Oliver; Nöllke, Peter; Krombholz, Christopher; Niemeyer, Charlotte; Plass, Christoph; Flotho, Christian
Abstract Background Juvenile myelomonocytic leukemia (JMML) is a myeloproliferative neoplasm of childhood whose clinical heterogeneity is only poorly represented by gene sequence alterations. It was previously shown that aberrant DNA methylation of distinct target genes defines a more aggressive variant of JMML, but only few significant targets are known so far. To get a broader picture of disturbed CpG methylation patterns in JMML, we carried out a methylation screen of 34 candidate genes in 45 patients using quantitative mass spectrometry. Findings Five of 34 candidate genes analyzed showed recurrent hypermethylation in JMML. cAMP-responsive element-binding protein-binding protein (CREBBP ) was the most frequent target of epigenetic modification (77 % of cases). However, no pathogenic mutations ofCREBBP were identified in a genetic analysis of 64 patients.CREBBP hypermethylation correlated with clinical parameters known to predict poor outcome. Conclusions This study supports the relevance of epigenetic aberrations in JMML pathophysiology. Our data confirm that DNA hypermethylation in JMML is highly target-specific and associated with higher-risk features. These findings encourage the development of prognostic markers based on epigenetic alterations, which will be helpful in the difficult clinical management of this heterogeneous disease.